4D Mapping of the Fracture Evolution in a Printed Gypsum-Like Core by Using X-Ray CT Scanning - Huabo Liu; Fanjing Meng; Shaozhen Hua (Advances in Civil Engineering)
The paper presents the use of micro-X-ray computed tomography (CT) system and associated automatic loading device in visualizing and analyzing the propagation of penny-shaped flaw in gypsum-like 3D printing specimen. During the loading process, a micro-X-ray computed tomography (CT) system was used to scan the specimen with a resolution of 30 × 30 μm2. The volumetric images of specimen were reconstructed based on two-dimensional images. Thus, the propagation of penny-shaped flaw in gypsum-like 3D printing specimen in spatial was observed. The device can record the evolution of the internal penny-shaped flaw by X-ray CT scanning and the evolution of the surface crack by digital radiography at the same time. Fractal analysis was employed to quantify the cracking process. Two- and three-dimensional box-counting methods were applied to analyze slice images and volumetric images, respectively. Comparison between fractal dimensions calculated from two- and three-dimensional box-counting method was carried out. The results show that the fractal dimension increases with the propagation of cracks. Moreover, the common approach to obtain the 3D fractal dimension of a self-similar fractal object by adding one to its corresponding 2D fractal dimension is found to be inappropriate.